Effectiveness of pelvic rocking exercise on length and pain in delivery women: A Meta-Analysis - Zesika Intan Navelia; Heru Subaris Kasjono; Mahindria Vici Virahaju (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2022)
Background: Anxiety about prolonged and painful labor processes encourages the mother to do a section cesarean ( SC ), which is becoming one of the indications SC incidents increase globally. Pelvic rocking exercise using a birth ball has several benefits in helping mothers give birth, especially in the first stage. The movement by sitting on the ball and rocking using gravity can increase the release of endorphins that provide comfort and enhance duration in labor.Objectives: To analyze the effectiveness of the pelvic rocking exercise using a birth ball on the duration of labor and reducing pain in the first stage of labor.Methods: A systematic review and meta-analysis by conducting an article search strategy using an electronic database according to the PICO method by eliminating articles according to the inclusion criteria includes articles with a period of 2011 – 2021, in Indonesian or English, using the RCT or Quasy experimental method, and the respondents used are pregnant women with gestational age of 30 weeks and above..Results: PRE using birth ball obtained statistically proven results to shorten the length and reduce labor pain than the control group. The experimental group had a significant effect in reducing labor duration and pain after intervention -1.13 [95% CI: -1.57, -0.09] p<0.00001 and -1.19 [95% CI: -1.48, -0.90] p <0.00001.Conclusions: There is an effect of pelvic rocking exercise using a birth ball on decreasing length of labor and pain in the first stage phase. It is expected that this research can be a complementary therapy option with good benefits and easy procedures for independent and collaborative midwifery practice in providing comprehensive midwifery care